Advancing Graphene Synthesis: Low-Temperature Growth and Hydrogenation Mechanisms Using Plasma-Enhanced Chemical Vapor Deposition - Šarūnas Meškinis; Algirdas Lazauskas; Šarūnas Jankauskas; Asta Guobienė; Rimantas Gudaitis (Molecules)
This study explores the low-temperature synthesis of graphene using plasma-enhanced chemical vapor deposition (PECVD), emphasizing the optimization of process parameters to achieve controlled growth of pristine and hydrogenated graphene. Graphene films were synthesized at temperatures ranging from 700 °C to as low as 400 °C by varying methane (25–100 sccm) and hydrogen (25–100 sccm) gas flow rates under 10–20 mBar pressures. Raman spectroscopy revealed structural transitions: pristine graphene grown at 700 °C exhibited strong 2D peaks with an I(2D)/I(G) ratio > 2, while hydrogenated graphene synthesized at 500 °C showed increased defect density with an I(D)/I(G) ratio of ~1.5 and reduced I(2D)/I(G) (~0.8). At 400 °C, the material transitioned to a highly hydrogenated amorphous carbon film, confirmed by photoluminescence (PL) in the Raman spectra. Atomic force microscopy (AFM) showed pristine graphene with a root mean square roughness (Rq) of 0.37 nm. By carefully adjusting PECVD synthesis parameters, it was possible to tune the surface roughness of hydrogenated graphene to levels close to that of pristine graphene or to achieve even smoother surfaces. Conductive AFM measurements revealed that hydrogenation could enhance graphene’s contact current under specific conditions. The findings highlight the role of PECVD parameters in tailoring graphene’s structural, morphological, and electronic properties for diverse applications. This work demonstrates a scalable, low-temperature approach to graphene synthesis, offering the potential for energy storage, sensing, and electronic devices requiring customized material properties.